Strategies for Implementing Exemplary Values in Aqidah Akhlak Teaching for Madrasah Ibtidaiyah Negeri Students - Yemi Agusti; Alimni Alimni (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: The implementation of exemplary values in students' character education during Akidah Akhlak lessons, both at school and at home, is crucial for cultivating good behavior. However, applying these values outside the classroom remains challenging, particularly in terms of students' consistency in practicing the knowledge acquired at school within their home environment. Objective: This study aims to examine how exemplary values are implemented in Akidah Akhlak education among students at Madrasah Ibtidaiyah Negeri 05 Bengkulu Tengah.Method: A qualitative approach was employed, with data collected through observations, interviews, and documentation. Data analysis focused on understanding how exemplary values are applied both in the classroom and at home. Results: The findings indicate that the implementation of exemplary values by the third-grade teacher at school was effective and categorized as good. However, the application of knowledge at home remains limited, as students are less consistent in practicing what they have gained due to a lack of awareness and fear of parental authority. Conclusion: While the implementation of exemplary values at school is effective, support from the home environment is necessary to strengthen students' habit formation. Contribution: This study offers recommendations for teachers and parents to enhance the consistency of applying exemplary values, thereby ensuring that Akidah Akhlak education is more effective both in school and at home.